PELATIHAN PTK (PENELITIAN TINDAKAN KELAS) BAGI GURU SMA NEGERI 2 PLUS SIPIROK - Elisa, Elisa; Mardiyah, Ainun; Irwan, Nova (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Dedication activities are motivated by the importance of conducting classroom action research in making changes in improving the quality of education. The purpose of community service is to increase the interest of writing PTK for teachers and students create and innovative teachers have as an educator so that educator goals can be achieved. The formulation of the problem in this devotion is (1) How the teacher's fundamental knowledge about PTK. (2) How creativity and activity of teacher in writing. This religious activity is held for three meetings. The first meeting discusses fundamental knowledge of PTK by providing an initial skill test. The second meeting discusses the preparation of PTK proposals and the implementation of PTK. While at the third meeting discussed the processing of data results and preparation of the final report. Based on observations during community service activities, some positive results were obtained: (1) Participants showed very high attention to community service materials. (2) The participants actively asked in exposing the problems faced during this time when making PTK. (3) From the initial test consists of 20 questions about knowledge of PTK. From the initial data obtained, only two people or about 13.33% of teachers who can answer and get a score above the KKM, while 13 people or about 86.7% of teachers have not been able to answer and earn, score below KKM. After the final test is obtained, almost all teachers around 98.97% of teachers can answer and score above KKM. The result of community service is increasing the insight of high school teacher N 2 Plus Sipirok on the preparation of PTK (classroom action research).Keywords: Classroom action Research, teacher, proposal.